Carbon quantum dot intercalation fluorinated graphene embedded structure lubricating additive and preparation method thereof

By inserting carbon quantum dots between the layers of fluorinated graphene nanosheets to form a layered structure lubricating additive, the problems of poor lubricating performance and serious wear in long-term operation of traditional lubricating materials are solved, and efficient anti-friction and anti-wear effects are achieved.

CN119614268AActive Publication Date: 2025-03-14SHAANXI UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411746948.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Traditional graphene-based lubricating materials have problems with poor lubricating performance and severe wear under long-term operating conditions, resulting in limited further application in the lubricating field.

Method used

Through electrostatic self-assembly method, carbon quantum dots (CQDs) are inserted between the layers of fluorinated graphene (FG) nanosheets to form carbon quantum dot intercalation layer fluorinated graphene intercalation structure lubricating additive.

Benefits of technology

It achieves excellent chemical stability, high friction and wear resistance of lubricating materials, and has good practicality and long-lasting lubricating properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614268A_ABST
    Figure CN119614268A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon quantum dot intercalation fluorinated graphene embedded structure lubricating additive and a preparation method thereof.The preparation method comprises the steps that sodium hydroxide and acetaldehyde are taken to be mixed and fully stirred and then subjected to ultrasonic treatment until floccules appear, a final product is dried in a freeze dryer, and CQDs powder is obtained; the preparation method comprises the following steps: dissolving hexadecyl trimethyl ammonium bromide and graphite fluoride in deionized water, and carrying out ball milling to obtain exfoliated FG-CTA < + > dispersion liquid; dispersing CQDs powder in deionized water, adding into the stripped FG-CTA + dispersion liquid, carrying out ultrasonic treatment on mixed slurry, putting the mixture into a flask, heating at 80-120 DEG C for 6-10 hours, then adding 0.2-0.6 g of ascorbic acid, reducing at 80-100 DEG C for 6-10 hours, filtering, washing, and drying to obtain the CQDs / CTA composite material. And finally, solid is separated out, cleaned and freeze-dried to obtain the carbon quantum dot intercalation fluorinated graphene embedded structure lubricating additive with excellent friction resistance and wear resistance, and the lubricating additive has durable and excellent lubricating performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, relates to a nano-composite lubricating material and a preparation method thereof, and specifically relates to a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive and a preparation method thereof. Background Art

[0002] With the continuous advancement of industrial technology, the performance requirements for lubricating materials are getting higher and higher. Especially under long-term operating conditions, traditional graphene-based lubricating materials often face the problems of poor lubrication performance and severe wear, which restricts their further application in the field of lubrication. This can be attributed to poor dispersion stability and insufficient antioxidant properties. First, the layered structure of graphene is easy to stack during repeated friction, reducing its effective contact area, thereby reducing the anti-wear and anti-friction effects. Secondly, in actual use, graphene additives also have obvious adverse effects such as complex oxides and smoke in engine lubricating oils, limiting their potential to improve the antioxidant properties of lubricating oils. Therefore, the durability and reliability of lubricating materials required by continuously running mechanical parts cannot be met. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive with excellent chemical stability, high anti-friction and anti-wear effects and a preparation method thereof. As a lubricating additive, it has durable and excellent lubricating properties and a simple preparation process.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A method for preparing a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive comprises the following steps:

[0006] Step 1: Sodium hydroxide and acetaldehyde are taken at a mass volume ratio of (4-8) g: (10-30) mL. Acetaldehyde is first added to a beaker, and sodium hydroxide is slowly added and stirred for 1-3 hours. Then, the mixture is ultrasonically treated with dilute hydrochloric acid until floccules appear. The final product is dried in a freeze dryer to obtain CQDs powder.

[0007] Step 2: Take 0.8 g of hexadecyltrimethylammonium bromide and 0.1-0.3 g of graphite fluoride and dissolve them in 30-50 mL of deionized water, and ball mill them in a ball mill for 5-10 hours to obtain exfoliated FG-CTA. + Dispersion liquid;

[0008] Step 3: Disperse 0.8-2.4 g of the CQDs powder prepared in step 1 in 20 mL of deionized water and add the exfoliated FG-CTA +In the dispersion, the mixed slurry is ultrasonically treated for 3 to 5 hours, and then 0.2 to 0.6 g of ascorbic acid is added, and the mixture is placed in a flask and heated at 80 to 120° C. for 6 to 10 hours. Finally, the solid is separated, washed, and freeze-dried to obtain a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive.

[0009] The present invention also has the following technical features:

[0010] Preferably, the dilute hydrochloric acid in step 1 is prepared by mixing hydrochloric acid with a purity of 37% and deionized water in a volume ratio of 1:1.

[0011] Preferably, the ultrasonic frequency of the ultrasonic treatment in step 1 and step 3 is 40KHz to 60KHz.

[0012] Preferably, the freeze-drying time in step 1 and step 3 is 36 to 60 hours.

[0013] Preferably, the ball mill described in step 2 has a rotation speed of 400 to 600 rpm during ball milling.

[0014] The present invention also protects a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive prepared by the method as described above.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The present invention successfully confines graphene / reduced carbon quantum dots (FG / rCQDs) between the layers of graphene nanosheets through an electrostatic self-assembly method, prepares an intercalation structure, and obtains a novel graphene / reduced carbon quantum dots (FG / rCQDs) hybrid material with ultra-large interlayer spacing and good lubrication performance; under the induction of friction and frictional heat, the FG / rCQDs prepared by the present invention exhibit friction effects at different friction stages: rolling effect, filling effect and friction film effect, and these effects work synergistically to achieve excellent and lasting lubrication performance:

[0017] In the early stage of friction, under the action of friction shear force, the intercalated structure FG / rCQDs formed a lubricating component similar to a "cart". Due to the existence of interlayer CQDs, sliding friction can be converted into rolling friction, significantly reducing the friction coefficient; as the friction progresses, fine wear tracks are generated on the friction interface. Under the action of shear force, the CQDs on the surface of FG / rCQDs will fall off, thereby generating many free CQDs in the friction gap; since CQDs are negatively charged, under the dual effects of thermal motion and charge attraction, the free CQDs will be attracted to the positively charged wear path, blocking the wear path, thereby It plays a filling role in the wear path; as the friction process deepens, the FG nanosheets undergo defluorination under the action of shear force and friction heat, producing a large number of free fluoride ions. At the same time, a large number of positive charges are generated between the friction pairs, and the fluoride ions are attracted to the friction pairs to form an adsorption layer composed of iron fluoride; fluorine has a strong electronegativity and is easy to combine with iron metal ions to form iron fluoride; compared with iron oxide, iron fluoride has the advantage of being more stable, thus playing a more lasting protective film role between the friction pairs, and plays a vital role in anti-wear and anti-friction; therefore, FG / rCQDs has good practicality as a lubricating additive;

[0018] The preparation process of the invention has the advantages of simple reaction process and does not require large-scale equipment and harsh conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is the TEM of FG and FG / rCQDs before and after composite prepared in Example 1;

[0020] Figure 2 is the XRD of FG and FG / rCQDs before and after composite prepared in Example 1;

[0021] Figure 3 is a dispersion stability picture of the FG / rCQDs / PAO dispersion prepared in Example 1;

[0022] Figure 4 It is the friction coefficient curve of different components prepared in Example 1. DETAILED DESCRIPTION

[0023] The present invention is specifically described below in conjunction with the accompanying drawings and Examples, but the embodiments of the present invention are not limited thereto. The reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods for which specific experimental conditions are not indicated in the following examples are usually in accordance with conventional experimental conditions. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.

[0024] The dilute hydrochloric acid used in the following examples is prepared by mixing hydrochloric acid with a purity of 37% and deionized water in a volume ratio of 1:1.

[0025] Embodiment 1:

[0026] Step 1: first add 20 mL of acetaldehyde into a beaker, slowly add 6 g of sodium hydroxide, and continue stirring for 2 h, then use dilute hydrochloric acid for ultrasonic treatment at a frequency of 40 KHz until floccules appear, and the final product is freeze-dried in a freeze dryer for 36 h to obtain CQDs powder;

[0027] Step 2: Dissolve 0.8 g of hexadecyltrimethylammonium bromide and 0.2 g of graphite fluoride in 30 mL of deionized water and mill at 400 rpm for 10 hours to obtain exfoliated FG-CTA. + Dispersion liquid;

[0028] Step 3: Take 1.6 g of the CQDs powder prepared in step 1 and disperse it in 20 mL of deionized water. Add the exfoliated FG-CTA + In the dispersion, the mixed slurry was ultrasonically treated for 3 hours at an ultrasonic frequency of 60 KHz, and then 0.6 g of ascorbic acid was added. The mixture was placed in a flask and heated at 100 ° C for 6 hours. Finally, the solid was separated, washed with distilled water and freeze-dried for 36 hours to obtain a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive.

[0029] Embodiment 2:

[0030] Step 1: first add 10 mL of acetaldehyde into a beaker, slowly add 6 g of sodium hydroxide, and continue stirring for 2 h, then use dilute hydrochloric acid for ultrasonic treatment at a frequency of 50 KHz until floccules appear. The final product is freeze-dried in a freeze dryer for 48 h to obtain CQDs powder;

[0031] Step 2: Dissolve 0.8 g of hexadecyltrimethylammonium bromide and 0.3 g of graphite fluoride in 30 mL of deionized water and mill at 400 rpm for 10 hours to obtain exfoliated FG-CTA. + Dispersion liquid;

[0032] Step 3: Take 1.6 g of the CQDs powder prepared in step 1 and disperse it in 20 mL of deionized water. Add the exfoliated FG-CTA + In the dispersion, the mixed slurry was ultrasonically treated for 3 hours at an ultrasonic frequency of 60 KHz, and then 0.2 g of ascorbic acid was added. The mixture was placed in a flask and heated at 80° C. for 8 hours. Finally, the solid was separated, washed with distilled water and freeze-dried for 36 hours to obtain a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive.

[0033] Embodiment 3:

[0034] Step 1: first add 20 mL of acetaldehyde into a beaker, slowly add 6 g of sodium hydroxide, and continue stirring for 3 h, then use dilute hydrochloric acid for ultrasonic treatment at a frequency of 40 KHz until floccules appear, and the final product is freeze-dried in a freeze dryer for 36 h to obtain CQDs powder;

[0035] Step 2: Dissolve 0.8 g of hexadecyltrimethylammonium bromide and 0.2 g of graphite fluoride in 30 mL of deionized water and mill at 400 rpm for 10 hours to obtain exfoliated FG-CTA. + Dispersion;

[0036] Step 3: Take 2.4 g of the CQDs powder prepared in step 1 and disperse it in 20 mL of deionized water. Add the exfoliated FG-CTA + In the dispersion, the mixed slurry was ultrasonically treated for 3 hours at an ultrasonic frequency of 60 KHz, and then 0.4 g of ascorbic acid was added. The mixture was placed in a flask and heated at 120° C. for 6 hours. Finally, the solid was separated, washed with distilled water and freeze-dried for 36 hours to obtain a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive.

[0037] Embodiment 4:

[0038] Step 1: first add 20 mL of acetaldehyde into a beaker, slowly add 6 g of sodium hydroxide, and continue stirring for 2 h, then use dilute hydrochloric acid for ultrasonic treatment at a frequency of 40 KHz until floccules appear. The final product is freeze-dried in a freeze dryer for 48 h to obtain CQDs powder;

[0039] Step 2: Dissolve 0.8 g of hexadecyltrimethylammonium bromide and 0.2 g of graphite fluoride in 30 mL of deionized water and mill at 400 rpm for 10 hours to obtain exfoliated FG-CTA. + Dispersion;

[0040] Step 3: Take 1.6 g of the CQDs powder prepared in step 1 and disperse it in 20 mL of deionized water. Add the exfoliated FG-CTA + In the dispersion, the mixed slurry was ultrasonically treated for 3 hours at an ultrasonic frequency of 60 KHz, and then 0.3 g of ascorbic acid was added. The mixture was placed in a flask and heated at 120° C. for 6 hours. Finally, the solid was separated, washed with distilled water and freeze-dried for 36 hours to obtain a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive.

[0041] Embodiment 5:

[0042] Step 1: first add 30 mL of acetaldehyde into a beaker, slowly add 8 g of sodium hydroxide, and continue stirring for 1 hour, then use dilute hydrochloric acid for ultrasonic treatment at an ultrasonic frequency of 60 KHz until floccules appear. The final product is freeze-dried in a freeze dryer for 60 hours to obtain CQDs powder;

[0043] Step 2: Dissolve 0.8 g of hexadecyltrimethylammonium bromide and 0.1 g of graphite fluoride in 40 mL of deionized water and mill at 500 rpm for 5 hours to obtain exfoliated FG-CTA. + Dispersion liquid;

[0044] Step 3: Take 0.8 g of the CQDs powder prepared in step 1 and disperse it in 20 mL of deionized water. Add the exfoliated FG-CTA + In the dispersion, the mixed slurry was ultrasonically treated for 4 hours at an ultrasonic frequency of 50 KHz, and then 0.5 g of ascorbic acid was added. The mixture was placed in a flask and heated at 80° C. for 10 hours. Finally, the solid was separated, washed with distilled water and freeze-dried for 48 hours to obtain a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive.

[0045] Embodiment 6:

[0046] Step 1: first add 20 mL of acetaldehyde into a beaker, slowly add 4 g of sodium hydroxide, and continue stirring for 2 h, then use dilute hydrochloric acid for ultrasonic treatment at a frequency of 40 KHz until floccules appear, and the final product is freeze-dried in a freeze dryer for 36 h to obtain CQDs powder;

[0047] Step 2: Dissolve 0.8 g of hexadecyltrimethylammonium bromide and 0.1 g of graphite fluoride in 30 mL of deionized water and mill at 600 rpm for 8 hours to obtain exfoliated FG-CTA. + Dispersion liquid;

[0048] Step 3: Take 1.6 g of the CQDs powder prepared in step 1 and disperse it in 20 mL of deionized water. Add the exfoliated FG-CTA + In the dispersion, the mixed slurry was ultrasonically treated for 5 hours at an ultrasonic frequency of 40 KHz, and then 0.2 g of ascorbic acid was added. The mixture was placed in a flask and heated at 100 ° C for 8 hours. Finally, the solid was separated, washed with distilled water and freeze-dried for 60 hours to obtain a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive.

[0049] The SEM and TEM images of FG and FG / rCQDs before and after composite prepared in Example 1 are as follows: Figure 1As shown in the figure, the morphological characteristics of FGi and FG / rCQDs can be seen: FGi before insertion presents a multilayer structure, which provides conditions for the insertion of CQDs. After intercalation treatment, CQDs are evenly distributed on the surface of FG nanosheets to form corresponding CQDs lattice stripes, so CQDs are embedded between FG nanolayers.

[0050] The XRD patterns of FG and FG / rCQDs before and after composite prepared in Example 1 are as follows: Figure 2 shown by Figure 2 It can be seen that all characteristic signals of multilayer FGi have a significant rightward shift in the (002) peak at 21.4°, reflecting the increase in interlayer spacing. This indicates that CQDs are successfully inserted into the FGi interlayers and the interlayer spacing is significantly extended from 0.42nm to 1.08nm. It is well documented that the interlayer spacing of 1.08nm is the largest among all studies.

[0051] The dispersion stability of the FG / rCQDs / PAO dispersion prepared in Example 1 is as follows: Figure 3 As shown. Figure 3 It can be seen that after standing for another day or even two days, the FG / rCQDs / PAO dispersion can still show good dispersion stability.

[0052] The friction coefficient curves of different components obtained in Example 1 are as follows: Figure 4 As shown. Figure 4 It can be seen that in the 30-min friction test, the friction coefficient of FG / rCQDs lubrication is significantly lower than that of other parts. Compared with mechanical mixing, the friction coefficient is reduced from 0.11 to 0.03.

[0053] It should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it; without departing from the concept of the present invention, the deduction or replacement made by those skilled in the art shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive, characterized in that: The following steps are involved: Step 1: Sodium hydroxide and acetaldehyde are taken at a mass volume ratio of (4-8) g: (10-30) mL. Acetaldehyde is first added to a beaker, and sodium hydroxide is slowly added and stirred for 1-3 hours. Then, the mixture is ultrasonically treated with dilute hydrochloric acid until floccules appear. The final product is dried in a freeze dryer to obtain CQDs powder. Step 2: Take 0.8 g of hexadecyltrimethylammonium bromide and 0.1-0.3 g of graphite fluoride and dissolve them in 30-50 mL of deionized water, and ball mill them in a ball mill for 5-10 hours to obtain exfoliated FG-CTA. + Dispersion liquid; Step 3: Disperse 0.8-2.4 g of the CQDs powder prepared in step 1 in 20 mL of deionized water and add the exfoliated FG-CTA + In the dispersion, the mixed slurry is ultrasonically treated for 3 to 5 hours, and then 0.2 to 0.6 g of ascorbic acid is added, and the mixture is placed in a flask and heated at 80 to 120° C. for 6 to 10 hours. Finally, the solid is separated, washed, and freeze-dried to obtain a carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive.

2. The method for preparing the carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive according to claim 1, characterized in that: The dilute hydrochloric acid described in step 1 is prepared by mixing hydrochloric acid with a purity of 37% and deionized water in a volume ratio of 1:

1.

3. The method for preparing the carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive according to claim 1, characterized in that: The ultrasonic frequency of the ultrasonic treatment described in step 1 and step 3 is 40KHz to 60KHz.

4. The method for preparing the carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive according to claim 1, characterized in that: The freeze drying time described in step 1 and step 3 is 36 to 60 hours.

5. The method for preparing the carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive according to claim 1, characterized in that: The ball mill described in step 2 has a rotation speed of 400 to 600 rpm during ball milling.

6. A carbon quantum dot intercalated fluorinated graphene intercalation structure lubricating additive prepared by the method as described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Graphene and carbon nitride quantum dot composite nanometer material, as well as lubricating oil friction improver

    CN105316077A

  • Water-based lubricant based on two-dimensional material nanosheets / carbon quantum dots and preparation method of water-based lubricant

    CN106520354A

  • Macroscopic-quantity preparation method of fluorinated graphene

    CN109160507A

  • Preparation method and application of carbon quantum dot / graphene / 2D Zn-MOF ternary nano lubricating additive

    CN114574266A

  • Lubrication additive for composite carbon material, super lubricating water lubricant, preparation method therefor, and application thereof

    WO2021243826A1